‘A prioritizing game’: coachability in Canadian parole workplace culture - Taylor, Micheal P. (Criminal justice studies, 2025)
In this article, we examine systemic challenges in Canada’s federal parole service through a qualitative study of organizational stressors, including job strain, role conflict, effort-reward imbalance, and status inconsistency based on interviews with 28 parole officers. Using a semi-grounded constructivist approach integrating appreciative inquiry and ethnomethodological insights, we explore carceral workplace culture across prison and community settings. Findings show how administrative harms, resource precarity, and a managerial focus on quantitative metrics create entropic conditions that undermine therapeutic relationships, organizational justice, and parole officers’ well-being. To address these challenges, we apply the theoretical framework of coachability, offering it as a deontological approach rooted in care ethics and organizational learning. Coachability fosters continuous improvement by aligning operational feedback with intrinsic motivations, enabling parole officers to navigate workplace stressors and enhance relational outcomes. By bridging occupational health determinants with organizational goals, we theorize that coachability can mitigate burnout, improve role clarity, and reimagine parole work as an equitable and sustainable system of resiliency potential. These findings contribute to scholarship on organizational citizenship behavior that advances a model of justice and human flourishing in contemporary parole work.